Golput dalam Pemilu Perspektif Hukum Politik Islam: Telaah Pemikiran Ali Muhammad al-Sallabi - Jiyadi, Mufid; Fahmi, Mutiara; Umur, Azmil (Prodi Tata Negara (Siyasah) IAIN Langsa, 2025)
This article discusses scholars' views on the law of not exercising the right to vote in general elections from the perspective of Islamic political law, especially in the view of Ali Muhammad Sallabi. This study arises from the existence of different scholarly perspectives in assessing the position of elections and citizens' attitudes in exercising their voting rights. For this reason, three aspects are discussed: first, the view of Ali Muhammad Sallabi regarding the law of not exercising the right to vote in the election process; second, the perspective of Islamic political law on Sallabi's view; third, the relevance of Sallabi's view to the concept of modern law. The approach used is a conceptual approach, with the type of normative legal research. Data comes from library legal materials collected through book survey techniques. Data analysis is prescriptive-analytic. The research findings show that Ali Muhammad Sallabi argues that in the context of the state, exercising the right to vote in elections is obligatory. His argument refers to Quranic principles, the practice of the Companions regarding leadership regeneration, and the concept of public interest. Sallabi's opinion aligns with the principles of Islamic political law because there is no evidence explicitly prohibiting or commanding the use of voting rights in elections, while exercising the right to vote brings benefits. Furthermore, Sallabi's view is relevant to the concept of modern law, where leadership elections are carried out through voting processes, and citizens exercise their voting rights as part of realizing democratic principles.